The association of self-reported awake bruxism with anxiety, depression, pain threshold at pressure, pain vigilance, and quality of life in patients undergoing orthodontic treatment - Naila Aparecida Godoi MACHADO; Yuri Martins COSTA; Henrique Muller QUEVEDO; Juliana STUGINSKI-BARBOSA; Caio Martins VALLE; Leonardo Rigoldi BONJARDIM; Daniela Gamba GARIB; Paulo César Rodrigues CONTI (University of São Paulo, 2020)
Abstract This study aimed to evaluate whether the presence of awake bruxism was associated with temporomandibular dysfunction symptoms, pain threshold at pressure, pain vigilance, oral health-related quality of life (OHRQoL), and anxiety and depression symptoms in patients undergoing orthodontic treatment. Methodology This observational study followed patients who had started receiving orthodontic treatment for six months. The following variables were measured three times (at baseline, one month, and six months): pressure pain threshold (PPT) in the right and left masseter, anterior temporalis, and temporomandibular joint (TMJ), and right forearm; pain vigilance and awareness questionnaire; and shortened form of the oral health impact profile (OHIP-14). Anxiety and depression symptoms were measured using the Beck anxiety inventory and the Beck depression inventory, respectively. The patients were divided into two main groups according to the presence (n=56) and absence (n=58) of possible awake bruxism. The multi-way analysis of variance (ANOVA) was applied on the date (p=0.050). Results TMJ and/or muscle pain were not observed in both groups. Time, sex, age group, and awake bruxism did not affect the PPT in the masticatory muscles and pain vigilance (p>0.050). However, the primary effect of awake bruxism was observed when anxiety (ANOVA: F=8.61, p=0.004) and depression (ANOVA: F=6.48, p=0.012) levels were higher and the OHRQoL was lower (ANOVA: F=8.61, p=0.004). Conclusion The patients with self-reported awake bruxism undergoing an orthodontic treatment did not develop TMJ/masticatory muscle pain. The self-reported awake bruxism is associated with higher anxiety and depression levels and a poorer OHRQoL in patients during the orthodontic treatment.